Behaviour of sandwich panels subject to intense air blasts – Part 2: Numerical simulation - Karagiozova, D.; Nurick, G.N.; Langdon, G.S. (Composite structures, 2009)
Finite element simulation is employed to analyse the behaviour of clamped sandwich panels comprising equal thicknesses mild steel plates sandwiching an aluminium honeycomb core when subject to blast loadings. Pressure-time histories representative of blast loadings are applied to the front plate of the sandwich panel. The FE model is verified using the experimental test results for uniform and localised blast loading in the presence of a honeycomb core and with only an air gap between the sandwich plates. It is observed that for the particular core material, the load transfer to the back plate of the panel depends on the load intensity, core thickness and flexibility of the sandwich panels.